2014
DOI: 10.3748/wjg.v20.i42.15820
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy sparing in rectal cancer achieving complete response after chemoradiation

Abstract: Withholding adjuvant chemotherapy after complete response following standard neoadjuvant chemoradiotherapy and laparoscopic mesorectal excision might be safe within an experienced multidisciplinary team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, the rates of local and systemic recurrence vary significantly after radiotherapy, which illustrates that progression and resistance remain common events . Preoperative chemoradiotherapy results in fewer than 50% of rectal cancer patients achieving complete pathological response . Response to radiation is considered to be a key factor in the success of radiotherapy, but the response to radiation is determined by multifactorial etiologies (tumor pathologic type, tumor volume, tumor hypoxia, clinical stage, radiation dose and radiation modes) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the rates of local and systemic recurrence vary significantly after radiotherapy, which illustrates that progression and resistance remain common events . Preoperative chemoradiotherapy results in fewer than 50% of rectal cancer patients achieving complete pathological response . Response to radiation is considered to be a key factor in the success of radiotherapy, but the response to radiation is determined by multifactorial etiologies (tumor pathologic type, tumor volume, tumor hypoxia, clinical stage, radiation dose and radiation modes) .…”
Section: Discussionmentioning
confidence: 99%
“…136 A study in which patients who received neoadjuvant chemoRT and experienced a pCR were observed without additional adjuvant chemotherapy found 5-year DFS and OS rates of 96% and 100%, respectively. 221 In addition, a meta-analysis of 4 randomized trials (1,196 patients) concluded that adjuvant fluorouracil-based chemotherapy (5-FU/LV, capecitabine, or CAPEOX) after preoperative therapy and surgery did not improve OS, DFS, or the rate of distant recurrences in patients with stage II or III rectal cancer. 222 However, more recent trials that found a DFS benefit for the addition of adjuvant oxaliplatin-based adjuvant therapy were not included in this study, and other meta-analyses have come to the opposite conclusion.…”
Section: Watch-and-wait Approach For Clinical Complete Respondersmentioning
confidence: 99%
“…The lack of prospective studies to evaluate the effect of ACT is because a pCR is only achieved in ~10–20% of all rectal cancer patients 14,15 . Additionally, treatment adherence to ACT in this subpopulation is mostly poor given the possibility of treatment-related toxicity, financial burden, and a patient or clinician’s preference for less aggressive treatment 36 . In this clinical setting, a meta-analytic approach with a larger number of patients can help detect a small or absent treatment effect.…”
Section: Discussionmentioning
confidence: 99%